Mariah Devereux Herbeck. Wandering Women in French Film and Literature: A Study of Narrative Drift. New York: Palgrave Macmillan, 2013. - Melissa A Bailar (Studies in 20th & 21st Century Literature, 2017)
Review of Mariah Devereux Herbeck. Wandering Women in French Film and Literature: A Study of Narrative Drift. New York: Palgrave Macmillan, 2013.
Keywords: Book Review; Mariah Devereux Herbeck; Wandering Women in French Film and Literature: A Study of Narrative Drift